Sirt6-mediated Nrf2/HO-1 activation alleviates angiotensin II-induced DNA DSBs and apoptosis in podocytes. Issue 17 (9th July 2021) - Fan, Yanqin; Cheng, Jing; Yang, Qian; Feng, Jun; Hu, Jijia; Ren, Zhilong; Yang, Hongxia; Yang, Dingping; Ding, Guohua
Abstract : Sirt6 upregulation inhibited Ang II-induced ROS generation and DNA DSBs in podocytes, and it shows the cytoprotective effects in podocytes  via  the Nrf2/HO-1 pathway. Sirt6 may be a new therapeutic target for the treatment of CKD. Abstract : Recent studies suggested that DNA double-strand breaks (DSBs) were associated with the pathogenesis of chronic kidney disease (CKD). The purpose of this investigation was to determine the role of Sirtuin6 (Sirt6), a histone deacetylase related to DNA damage repair, in angiotensin (Ang) II-induced DNA DSBs and the cell injury of podocytes and explore the possible mechanism. Here we showed that an increase of DNA DSBs was accompanied by a reduction in Sirt6 expression in the glomeruli of patients with hypertensive nephropathy (HN). Similar results were found in rat kidneys infused with Ang II and in cultured podocytes stimulated with Ang II. Sirt6 overexpression inhibited Ang II-induced ROS generation and DNA DSBs, and thus served as a protection against Ang II-induced apoptosis in podocytes. Moreover, Sirt6 activation enhanced Nrf2 and HO-1 gene expressions in podocytes after Ang II treatment. Furthermore, Nrf2 knockdown could partly reverse the cytoprotective effects of Sirt6 activation. In conclusion, our observations demonstrated that the Sirt6-Nrf2-HO-1 pathway played a vital role in relieving Ang II-mediated oxidative DNA damage and podocyte injury.